Franco Petracchi and the Divertimento Concertante per Contrabbasso e Orchestra by Nino Rota : a successful collaboration between composer and performer - Ritter, Alexandre (2010)
Between 1967 and 1971, Nino Rota (1911 - 1979) composed the Divertimento Concertante per Contrabbasso e Orchestra in honor of the legendary double bass soloist, pedagogue and conductor Franco Petracchi (b. 1937). This Divertimento is a four-movement work with the following movements: “Allegro,” “Marcia,” “Aria,” and “Finale.” The entire piece is approximately twenty-four minutes in length and it holds an important position in the 20th-century solo repertoire for double bass. The author has investigated the unique circumstances of the collaboration between Franco Petracchi and Nino Rota between 1967 and 1971, when Rota composed the Divertimento Concertante per Contrabbasso e Orchestra. Particular attention has been given to how this collaboration affected the compositional history, the style, and the specific technical challenges that are found in the Divertimento. The technical demands of the piece will be compared with the concepts and exercises found in Petracchi’s method for the double bass, Simplified Higher Technique. While the method itself was published later, Petracchi was already using its core concepts in his lessons at the time the Divertimento was composed, when he was the bass professor at the Bari conservatory and Rota its director. The author will then discuss a later stage in the collaboration between the composer and performer, which resulted in a significantly different second version of the Divertimento. To date, this second version has not been published but it remains the preferred version for Petracchi. A detailed commentary on how the two versions compare, as well as a series of interviews between the author and Petracchi are also included in the document.